A new approach for grafting plasticized cellulose acetate biodegradable plastic with maleic anhydride: Processing and characterization - Ehsan Pesaranhajiabbas; Amar K. Mohanty; M. Sameer Al‐Abdul‐Wahid; Manjusri Misra (SPE Polymers, 2024)
Abstract Grafting polymers with reactive maleic anhydride is a common approach for the synthesis of new material with the capability of acting as a compatibilizer in polymer blends. Accordingly, this research showed a new approach for grafting maleic anhydride onto renewable cellulose acetate using an initiator. The grafting process through extrusion showed good stability with continuous production of all grafted samples. Moreover, two different grafting processes, namely one‐step and two‐step processes, were shown to produce materials with very similar characteristics. Grafting of maleic anhydride onto cellulose acetate by reacting with its hydroxyl groups was confirmed by both Fourier transform infrared spectroscopy and nuclear magnetic resonance analysis. Rheological studies also demonstrated the enhanced flowability and lower viscosity of the grafted material in comparison to the plasticized cellulose acetate. Highlights Grafting maleic anhydride onto plasticized cellulose acetate by reactive extrusion. Detection of grafted maleic anhydride onto cellulose acetate through NMR analysis. High thermal stability of grafted materials. Significant reduction in viscosity of plasticized cellulose acetate after grafting